ANALISIS KINERJA SEKOLAH DALAM MEMINGKATKAN MUTU PENDIDIKAN MELALUI AKREDITASI (Studi Pada SMP Sekecamatan Saparua dan Saparua Timur) - Cynthia Lusye Sapulette (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2019)
his research aims to find out: (1) How does the school prepare to implement school accreditation, which starts with filling in the field of accreditation data "DIA"?, (2) are recommendations from the assessors who do the visitation of 8 Education standards?, (3) efforts made to ensure quality education, (4). What factors become a barrier to improving the quality of education through school accreditation?. The study uses a descriptive method of quality. Qualitatively, it indicates that (1) accreditation is essential to the quality of the school. There must be a working team in the school for the fulfillment of 8 SNP. Charging HIM Online as an early stage of school readiness for accreditation. (2) The Assessor recommendation helps the school to see its weakness, to be repaired to be even better. (3) The development of teachers capacity and education, the development of Sarpras, organizing the administration, focus on the development of students ' character to achieve achievement. Budget that focuses on school needs, engages in the midst of society, or engages the community in activities in the school. (4) Teachers are not motivated to perform their duties with the target time. Teachers are indifferent with existing developments, and do not want to improve their scientific skills. The senior teachers and almost retired, felt difficulties in Menyesuikan with the demands of the existing curriculum, all of which is a barrier in the process of achieving the quality of education in school. And the lack of budget becomes a barrier in supporting various work programs.Key words: School performance, education quality, accreditation